Solve (z-i)+(z+i)+(z-1)+(z-1)

Since we are dealing with complex numbers and taking its modulus, we can rewrite (z-i)=((-1)(i-z))=(i-z) doing the same for (z-1)=(1-z) we get (i-z)+(z+i)+(1-z)+(z-1)=(i+i+z-z+1+1+z-z) =(2i+2)=4 as we are taking its modulus.

Related Further Mathematics A Level answers

All answers ▸

How do I solve a simultaneous equation with more unknowns than equations?


Give the general solution of the second order ODE dy2/d2x - 4dy/dx + 3 = 0


How do I sketch accurate graphs for rational functions in a short amount of time? (I.e. A step by step guide of sketching graphs)


Find the general solution for the determinant of a 3x3 martix. When does the inverse of this matrix not exist?


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences